A novel homozygous variant in BMPR1B underlies acromesomelic dysplasia Hunter–Thompson type. (10th January 2018) - Ullah, Asmat; Umair, Muhammad; Muhammad, Dost; Bilal, Muhammad; Lee, Kwanghyuk; Leal, Suzanne M; Ahmad, Wasim
Abstract: Acromesomelic dysplasia is genetically heterogeneous group of skeletal disorders characterized by short stature and acromelia and mesomelia of limbs. Acromesomelic dysplasia segregates in an autosomal recessive pattern and is caused by biallelic sequence variants in three genes ( NPR2, GDF5, and BMPR1B ). A consanguineous family of Pakistani origin segregating a subtype of acromesomelic dysplasia called Hunter–Thompson was clinically and genetically evaluated. Genotyping of microsatellite markers and linkage analysis revealed a 7.78 Mb homozygous region on chromosome 4q22.3, which harbors BMPR1B . Sequence analysis of the gene revealed a novel homozygous missense variant (c.1190T > G, p.Met397Arg) that segregates with the disease phenotype within the family and produced a Logarithm of odds (LOD) score of 3.9 with the disease phenotype. This study reports on the first familial case of acromesomelic dysplasia Hunter–Thompson type. It is also the first report of BMPR1B underlying the etiology of acromesomelic dysplasia Hunter–Thompson type.